The Position of Customary Law in the Indonesian Judicial System: Between Tradition and Modernization - Pupu, Pupu Sriwulan Sumaya (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2025)
This study aims to examine the position of customary law within Indonesia’s judicial system in the context of the tension between legal tradition and modernization. Although customary law has been constitutionally recognized under Article 18B paragraph (2) of the 1945 Constitution and reinforced through several legal instruments—such as Law No. 39 of 1999 on Human Rights and Constitutional Court Decision No. 35/PUU-X/2012—its implementation in judicial practice remains suboptimal. In many cases, customary law is treated merely as a secondary consideration, lacking binding technical guidelines for law enforcement officers and judges. This research adopts a normative-qualitative approach, using descriptive and juridical analysis through literature review, statutory interpretation, and legal document analysis. As analytical tools, it employs the theory of legal pluralism by John Griffiths, the concept of interlegalities by Boaventura de Sousa Santos, and is complemented by Satjipto Rahardjo’s theory of progressive law. The findings reveal that the current recognition of customary law in Indonesia remains subordinated, reflecting a model of weak legal pluralism. While in several regions customary law is more accepted by local communities—due to its perceived fairness, speed, and contextual relevance—the national legal system has yet to effectively accommodate such legal diversity. Legal policy reform is therefore needed, including the enactment of the Draft Law on Indigenous Peoples (RUU Masyarakat Hukum Adat), the issuance of a Supreme Court Regulation (PERMA) on the application of customary law, and the revitalization of customary institutions as alternative dispute resolution forums.In conclusion, customary law is not merely a cultural legacy, but a living source of law that must be positioned as an equal partner within the national legal framework. Strengthening customary law will support the development of a pluralistic, inclusive, and socially just legal system in Indonesia.